Continuous Transversus Abdominis Plane Nerve Blocks: Does Varying Local Anesthetic Delivery Method—Automatic Repeated Bolus Versus Continuous Basal Infusion—Influence the Extent of Sensation to Cold?. (April 2017) - Khatibi, Bahareh; Said, Engy T.; Sztain, Jacklynn F.; Monahan, Amanda M.; Gabriel, Rodney A.; Furnish, Timothy J.; Tran, Johnathan T.; Donohue, Michael C.; Ilfeld, Brian M.
Abstract : BACKGROUND: It remains unknown whether continuous or scheduled intermittent bolus local anesthetic administration is preferable for transversus abdominis plane (TAP) catheters. We therefore tested the hypothesis that when using TAP catheters, providing local anesthetic in repeated bolus doses increases the cephalad-caudad cutaneous effects compared with a basal-only infusion. METHODS: Bilateral TAP catheters (posterior approach) were inserted in 24 healthy volunteers followed by ropivacaine 2 mg/mL administration for a total of 6 hours. The right side was randomly assigned to either a basal infusion (8 mL/h) or bolus doses (24 mL administered every 3 hours for a total of 2 bolus doses) in a double-masked manner. The left side received the alternate treatment. The primary end point was the extent of sensory deficit as measured by cool roller along the axillary line at hour 6 (6 hours after the local anesthetic administration was initiated). Secondary end points included the extent of sensory deficit as measured by cool roller and Von Frey filaments along the axillary line and along a transverse line at the level of the anterior superior iliac spine at hours 0 to 6. RESULTS: Although there were statistically significant differences between treatments within the earlier part of the administration period, by hour 6 the difference in extent of sensory deficit to cold failed to reach statistical significance along the axillary line (mean = 0.9 cm; SD = 6.8; 95% confidence interval –2.0 to 3.8; P = .515) and transverse line (mean = 2.5 cm; SD = 10.1; 95% confidence interval –1.8 to 6.8; P = .244). Although the difference between treatments was statistically significant at various early time points for the horizontal, vertical, and estimated area measurements of both cold and mechanical pressure sensory deficits, no comparison remained statistically significant by hour 6. CONCLUSIONS: No evidence was found in this study involving healthy volunteers to support the hypothesis that changing the local anesthetic administration technique (continuous basal versus hourly bolus) when using ropivacaine 0.2% and TAP catheters at 8 mL/h and 24 mL every 3 hours significantly influences the cutaneous effects after 6 hours of administration. Additional research is required to determine whether changing variables (eg, local anesthetic concentration, basal infusion rate, bolus dose volume, and/or interval) would provide different results.